DAMPAK PSIKOLOGIS SISWA KORBAN BULLYING DI SMA NEGERI 1 BARUMUN - Erlina Harahap; Nor Mita Ika Saputri (Universitas Muhammadiyah Tapanuli Selatan, 2019)
Abstract: The purpose of this study was to determine the psychological impact of victims of bullying on students of SMA Negeri 1 Barumun. Respondents in this study were two people who were taken purposively by criteria: a) women / men victims of bullying, b) class X da XI. Informants in this study were parents, teachers and one friend of each research respondent. This research method is qualitative with a phenomenological approach. Data collection techniques are carried out by observation, interviews, and documentation. Phenomenology data analysis stages are: 1) data organization, 2) coding and analysis, 3) testing of guesses, 4) important things as analysis strategies. The results of the study are: 1) the forms of bullying experienced by the subject in school are the three forms of bullying namely physical, verbal, and psychological bullying; 2) factors that cause students to be bullied, which tend to be due to students who are physically small and weak, students who lack confidence, are difficult to adjust to the environment, and are considered unattractive in adolescents such as students with brown skin, curly hair, and others; 3) bullying in schools has an impact that can hinder the development of students at school, victims of bullying are afraid and then withdraw from their classmates, become passive and feel less focused on participating in classroom teaching and learning activities. Keywords: psychological impact, bullying Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui dampak psikologis korban bullying pada siswa SMA Negeri 1 Barumun. Responden dalam penelitian ini adalah dua orang yang diambil secara purposive dengan kriteria : a) perempuan/laki-laki korban bullying, b) kelas X da XI. Informan dalam penelitian ini adalah orangtua, guru dan satu orang teman dari setiap responden penelitian. Metode penelitian ini adalah kualitatif dengan pendekatan fenomenologis. Teknik pengumpulan data dilakukan dengan observasi, wawancara, dan dokumentasi. Tahapan analisis data fenomenologi adalah : 1) organisasi data, 2) koding dan analisis, 3) pengujian terhadap dugaan, 4) hal-hal penting sebagai strategi analisis. Hasil penelitian adalah: 1) bentuk bullying yang dialami subjek di sekolah adalah ketiga bentuk bullying yaitu bullying fisik, verbal, dan psikologis; 2) faktor yang menyebabkan siswa dibully yaitu cenderung dikarenakan adanya siswa yang mempunyai fisik kecil dan lemah, siswa yang kurang percaya diri, susah menyesuaikan dengan lingkungan, dan dianggap tidak menarik di lingkungan usia remaja seperti siswa yang mempunyai kulit sawo matang, rambut ikal, dan lain sebagainya; 3) bullying di sekolah mempunyai dampak yang dapat menghambat perkembangan siswa di sekolah, korban bullying merasa takut lalu menarik diri dari teman-teman di kelas nya, menjadi pasif dan merasa kurang fokus mengikuti kegiatan belajar mengajar di kelas. Kata kunci : dampak psikologis, bullying